Dynamics of Bridges, Volume 5 Proceedings of the 28th IMAC, A Conference on Structural Dynamics, 2010 - Proulx, Tom.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This the fifth volume of five from the 28th IMAC on Structural Dynamics and Renewable Energy, 2010, brings together 19 chapters on the Dynamics of Bridges. It presents early findings from experimental as well as computational investigations on the Dynamics of Bridges, including studies on Modeling Environmental Effects on the Dynamic Characteristics of the Tamar Suspension, Structural Health Monitoring of Bridges, Structural Assessment of Damaged Bridges Using Ambient Vibration Testing, and Development of a Tamar Bridge Finite Element Model.
Keywords: Engineering; Mechanical engineering; Engineering design; Civil engineering; Engineering; Structural Mechanics; Engineering Design; Civil Engineering